A new species of the genus Lichenomima Enderlein, 1910 (Psocodea: ‘Psocoptera’: Myopsocidae) from India - Ramesh, Gurusamy; Babu, Rajappa; Subramanian, Kumarapuram A. (Zootaxa, 2023)
Lichenomima aldretei n. sp. is described and depicted here and collected from the forests of the Western Ghats of Tamil Nadu, India, and is distinguished by a distinctive apical lobe in the hypandrium.